Improving the Quality of the Leaves and Seeds of Rubber Trees (Hevea brasilliensis) for Poultry Feed Through Various Types of Microbial Biotechnology - Syahruddin, Erman; Herawaty, R.; Azhar, (Pakistan Journal of Nutrition, 2016)
Objective: This study aims to determine the ability of some microbes to reduce the nutrients and crude fiber from the leaves and seeds of the rubber tree (Hevea brasilliensis) at various temperatures after a long fermentation. Methodology: This study was a laboratory experiment to measure the effects of multiple microbial fermentation times and temperatures on the nutrient content of the leaves and seeds of the rubber tree. The design used was a completely randomized 3×3×3 factorial design. The first factor is the type of microbe (Trichoderma spiralis, Rhizopus oligosporus and Neurospora sitophila). The second factor is the temperature (24, 34 and 44°C). The third factor is the fermentation time (2, 5 and 8 days). The best of the substrate proximate in the inoculum is then analyzed and calculated to determine the metabolizable energy and protein. Results: The nutrients of the leaves and seeds were compared after processing via rubber processing technology using fermentation with Trichoderma with other treatments and without fermentation. Conclusion: The quality of its nutritional value can be improved, namely, through an increase in the crude protein content of 60.67%, amounting to 32.58% nitrogen retention and 36.67% energy metabolism and a decline in the crude fiber content of 39.02%.